Platońska eudajmonia. Autor Politei o życiu szczęśliwym - Zbigniew Danek (Peitho, 2022)
The article deals with several issues related to the concept of happiness that emerge from Plato’s triptych: the Gorgias, the Republic and the Laws. The focus is on (1) the question of the alleged overcoming of the eudaimonistic imperative, i.e., natural human pursuit of happiness, in the didactic message of the Republic; (2) the question of to what extent the path of cognition ending in the contemplation of the perfect being is at the same time a strive for the supreme happiness; (3) the dilemma of choosing between a reductive and a cumulative model of complete satisfaction in human life; and finally (4) the problem of affiliative conditions of full life satisfaction.